2006
DOI: 10.1055/s-2005-858876
|View full text |Cite
|
Sign up to set email alerts
|

Low Prevalence of Chronic Hepatitis C, but High Prevalence of Elevated Aminotransferases in a Cohort of 2026 Patients Referred for Orthopaedic Surgery in the Eastern Part of Germany

Abstract: The prevalence of chronic hepatitis C is low in the investigated cohorts of orthopaedic patients in Thuringia and Saxonia. However, elevation of aminotransferases occurs surprisingly often. The reasons for elevated aminotransferases and a reliable analysis of the HCV prevalence in different subgroups of the Eastern German population require further evaluation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
7
1
3

Year Published

2006
2006
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 10 publications
2
7
1
3
Order By: Relevance
“…This observation matched with the lower frequency of reported patients to the German health authorities for reportable diseases, the Robert Koch Institute (RKI) [2], and a recently published survey on HCV-infected patients from various regions within Germany [3]. However, low awareness could account for low diagnosis rates; therefore, the latter two studies only indirectly confirmed our initial observation [1].…”
Section: Introductionsupporting
confidence: 92%
See 1 more Smart Citation
“…This observation matched with the lower frequency of reported patients to the German health authorities for reportable diseases, the Robert Koch Institute (RKI) [2], and a recently published survey on HCV-infected patients from various regions within Germany [3]. However, low awareness could account for low diagnosis rates; therefore, the latter two studies only indirectly confirmed our initial observation [1].…”
Section: Introductionsupporting
confidence: 92%
“…In an earlier study, we evaluated 2026 patients from East German orthopaedic surgeries, and recorded a 0.15% prevalence rate of HCV-RNA positivity [1]. This observation matched with the lower frequency of reported patients to the German health authorities for reportable diseases, the Robert Koch Institute (RKI) [2], and a recently published survey on HCV-infected patients from various regions within Germany [3].…”
Section: Introductionmentioning
confidence: 89%
“…Through a detailed review of published literature and the analysis of subpopulations, an anti‐HCV prevalence estimate of 0.5% (0.3–0.9%), corresponding to 410 000 (246 000–738 000) anti‐HCV infections, was estimated for 2012 (Table ) . A national study conducted in 2011, the German Health Interview and Examination Survey for Adults (DEGS1), estimated the anti‐HCV prevalence to be 0.3% (0.1–0.5%) .…”
Section: Resultsmentioning
confidence: 99%
“…Die Prävalenz der Hepatitis C weist in Deutschland deutliche regionale Unterschiede auf, z. B. geringere Häufigkeiten in den neuen Bundesländern, die mit einem zu Zeiten der DDR gegenüber Westdeutschland niedrigeren i. v. Drogenkonsum zusammenhän-gen kçnnten [9]. Darüber hinaus weicht die Prävalenz der HCVInfektion in einzelnen Personengruppen deutlich von der Allgemeinbevçlkerung ab.…”
unclassified